Adolescent Virtual Time Spent Socializing With Peers, Substance Use, and Delinquency. (October 2015) - Meldrum, Ryan C.; Clark, Jim
This study tests Osgood, Wilson, O'Malley, Bachman, and Johnston's extension of the routine activity theory of individual deviant behavior by considering adolescent time spent socializing with peers in virtual settings in relation to estimates of delinquency and substance use. The growth in digital communication has significantly changed the ways that youth commonly communicate with one another, and such changes may therefore provide a specification of newly emerging situational inducements that precipitate antisocial behavior during adolescence. Using data from a school-based survey of adolescents, the analyses reveal that the amount of virtual time adolescents spend socializing with peers is positively related to the frequency of alcohol use, marijuana use, and a variety index of delinquent behavior. Less support was found for an association between virtual time spent with peers and individually separated property/violent offending behaviors. The implications of these findings are discussed.